Gender Mainstreaming dalam al-Qur’an dan Hadis serta Relevansinya Terhadap Epistemologi Hukum Islam - Athoillah Islamy (Jurnal Hukum Islam, 2017)
This study explains about principle of gender relation on the main resource of Islamic law (Qur’an-Hadith) and their implications in the epistemology of Islamic law. This study states that the Qur’an and Hadith have the same moral message in respecting and upholding the principle of gender equality in all aspects of life. Therefore, it’s principle should be used as principle on the interpretation of Qur’an and Hadith in finding the contruction of Islamic legal doctrine whic is fair gender.